Answer: f(2) = 6
Step-by-step explanation: In this problem, we are given the function
f (x) = (x + 1) 2 and we are asked to find f(2). In other words, if we put an "x" into our function, we get a (x + 1) 2 out.
f we put a 2 into the function, we get f(2) = (2 + 1) 2 out. Now all we have to do is simplify on the right side.
2 + 1 gives us 3 and if we multiply 3 by 2, we get a product of 6.
Therefore, f(2) is 6.
Two brownies among three friends.
3/2 is 1.5
So 1.5 for the first friend, 1.5 for another friend, and 1.5 for the other friend.
Answer:
ross-multiplication.
circumference divided by the diameter
10/x = 580/185
10x185=1850
1850/580=3.189
Step-by-step explanation:
give me brainliest
Answer: 5x-7
Step-by-step explanation: